Modelling A Complex Human Centre Queuing System for Enhancing The Capability of Agent Based Simulation - Mazlina, Abdul Majid; Kamal Z., Zamli; Fakhreldin, Mohammed Adam Ibrahim (2015)
Agent Based Simulation (ABS) is a simulation technique that emerged after Discrete Event Simulation (DES). The design of ABS is based on artificial intelligence using the concept of robotics and multi-agent systems (MAS). The agent based model consists of a set of interacting active objects that reflect objects and relationships in the real world. Technically, every agent has its own thread of execution to represent its own histories, intentions, desires, individual properties, and complex relationships. ABS is found suitable to model people centric systems as compared to traditional DES. People centric systems are systems that involve with many human interactions and where the actors work with some degree of autonomy. However due to the MAS structure, agents in ABS are decentralized. As such, modeling people centric system’s features such as people queuing in ABS is found difficult. Addressing the aforementioned issue, we propose to enhance the capability of ABS for modelling human centric queuing system by combining DES approach in ABS model called hybrid ABS/DES model.